Accuracy of MDCT and CBCT in three-dimensional evaluation of the oropharynx morphology. (27th April 2017) - Chen, Hui; van Eijnatten, Maureen; Aarab, Ghizlane; Forouzanfar, Tim; de Lange, Jan; van der Stelt, Paul; Lobbezoo, Frank; Wolff, Jan
Summary: Objective: To assess the accuracy of five different computed tomography (CT) scanners for the evaluation of the oropharynx morphology. Methods: An existing cone-beam computed tomography (CBCT) data set was used to fabricate an anthropomorphic phantom of the upper airway volume that extended from the uvula to the epiglottis (oropharynx) with known dimensions (gold standard). This phantom was scanned using two multi-detector row computed tomography (MDCT) scanners (GE Discovery CT750 HD, Siemens Somatom Sensation) and three CBCT scanners (NewTom 5G, 3D Accuitomo 170, Vatech PaX Zenith 3D). All CT images were segmented by two observers and converted into standard tessellation language (STL) models. The volume and the cross-sectional area of the oropharynx were measured on the acquired STL models. Finally, all STL models were registered and compared with the gold standard. Results: The intra- and inter-observer reliability of the oropharynx segmentation was fair to excellent. The most accurate volume measurements were acquired using the Siemens MDCT (98.4%; 14.3 cm 3 ) and Vatech CBCT (98.9%; 14.4 cm 3 ) scanners. The GE MDCT, NewTom 5G CBCT, and Accuitomo CBCT scanners resulted in smaller volumes, viz ., 92.1% (13.4 cm 3 ), 91.5% (13.3 cm 3 ), and 94.6% (13.8 cm 3 ), respectively. The most accurate cross-sectional area measurements were acquired using the Siemens MDCT (94.6%; 282.4 mm 2 ), Accuitomo CBCT (95.1%; 283.8 mm 2 ), and Vatech CBCT (95.3%; 284.5 mm 2 ) scanners. The GE MDCT and NewTom 5G CBCT scanners resulted in smaller areas, viz ., 89.3% (266.5 mm 2 ) and 89.8% (268.0 mm 2 ), respectively. Limitations: Images of the phantom were acquired using the vendor-supplied default airway scanning protocol for each scanner. Conclusion: Significant differences were observed in the volume and cross-sectional area measurements of the oropharynx acquired using different MDCT and CBCT scanners. The Siemens MDCT and the Vatech CBCT scanners were more accurate than the GE MDCT, NewTom 5G, and Accuitomo CBCT scanners. In clinical settings, CBCT scanners offer an alternative to MDCT scanners in the assessment of the oropharynx morphology.